The association between government shareholding and family shareholding with corporate governance quality / Afifah Abdulloh - Abdulloh, Afifah (2013)
The objective of this study is to examine the association between government shareholding and family shareholding with corporate governance. The sample includes 638 Malaysian Public Listed Companies (PLCs) from main market and Ace market. This study using principal component analysis scoring to measure corporate governance quality by focusing on corporate governance items which consist of board size, ratio of non-executive director in the board, ratio of independent director in the board, board meeting, CEO duality, the numbers of the numbers of audit committee meeting, audit committee size and ratio of financial expert in audit committee. Consistent with prior findings, the study finds a positive relation between government shareholding and corporate governance quality. This suggest that the higher percentage of government shareholding, the higher corporate governance quality. On the other hand, there is a significant negative relationship between percentage of family shareholding and corporate governance quality, indicating that, firm with higher family shareholding has lower corporate governance quality. The result is robust even after including various controls such as leverage, firm size, growth, and return on assets, auditor and industry effect. This study concludes that share ownerships are important determinant of corporate governance quality